Prospective Study on Dynamic Postural Stability in Youth Competitive Alpine Skiers: Test-Retest Reliability and Reference Values as a Function of Sex, Age and Biological Maturation - Kiers, Kirsten; Ellenberger, Lynn; Jermann, Julia; Oberle, Felix; Frey, Walter O.; Spörri, Jörg (Frontiers in Physiology, 2022)
This study aimed (1) to assess the test-retest reliability of dynamic postural stability index (DPSI) assessments using a ski-specific jump protocol that consists of single-leg landings on a three-dimensional force plate after forward-performed double-leg drop jumps from a box over a hurdle (DJSLLs), (2) to provide reference values for female and male youth competitive alpine skiers; (3) to explore their changes in DPSI over 3 years during adolescence; and (4) to investigate potential associations of DPSI with age and biological maturation. Using three-dimensional force plates, 16 healthy subjects were tested on the same day (test-retest reliability experiment; five test-retest assessments of right leg landings), and 76 youth skiers aged 13 to 15 years were tested 3 times within 2 years (main experiment; average of two trials per leg each time). The test-retest reliability experiment revealed an ICC(3,1) and 95% CI of 0.86 [0.74, 0.94] for absolute DPSI assessment. The within-subject SEM of absolute DPSI was 16.30 N [13.66 N, 20.65 N], and the standardized typical error was moderate (0.39 [0.33, 0.50]). Both absolute and relative DPSI values were comparable between male and female youth competitive alpine skiers. The mean absolute DPSI in year 1 (195.7±40.9 N), year 2 (196.5±38.9 N) and year 3 (211.5±41.3 N) continuously increased (i.e., worsened) (p<0.001). Mean relative, i.e. body weight force normalized, DPSI values significantly decreased, i.e., improved, from year 1 to 2 (0.42±0.01 vs. 0.36±0.004; p<0.001) and year 1 to 3 (0.42±0.01 vs. 0.36±0.01; p<0.001). Absolute DPSI correlated with age and biological maturation, while no such correlations were found for relative DPSI values. Our findings suggest that DPSI is a reliable and sensitive measure of dynamic postural control during DJSLLs and that relative DPSI improves annually in competitive youth skiers when accounting for body weight. Future work should consider biological maturation testing during the growth spurt, and normalizing to body weight force could be a possible solution.